Investasi Halal di Pasar Modal: Alternatif Investasi di Masa Pandemi - Sholiha, Imroatus (Al-tsaman : Jurnal Ekonomi dan Keuangan Islam, 2021)
ABSTRACTThe covid-19 pandemic, which is a pandemic that has shaken not only the health of the world's people, but also the world's economy. As a result of this virus, household consumption or people's purchasing power, which is the pillar of 60 percent of the economy, fell quite deep, investment weakened because many businesses had stopped and so on. However, in the Islamic capital market, Islamic securities are more resilient during this pandemic. Sharia shares recorded an increase in July 2020, with JII constituents amounting to 1,852,320.46, ISSI constituents amounting to 3,013,152.02, and JII70 constituents amounting to 2,244,900.44. And for corporate sukuk, there was also an increase in July 2020, the outstanding value of sukuk was 30.04 trillion with 149 outstanding sukuk. And the accumulated value of sukuk issuance was 51.19 trillion with the accumulated number of sukuk issuances of 252. Corporate sukuk increased compared to 2019 , the outstanding value of sukuk is 29.83 trillion with 143 outstanding sukuk. And the accumulated value of issuance is 48.24 trillion with the accumulated number of sukuk issuances of 232. Meanwhile, sharia mutual funds also increased from 2019 to 2020, which in In 2019, the number of Sharia Mutual Funds was 265 with a NAV of Sharia Mutual Funds of 53.74 trillion. Meanwhile, in 2020 the number of Sharia Mutual Funds is 282 with a NAV of Sharia Mutual Funds of 63.52 trillion.Keywords: Alternative, investment, pandemic